Pemberdayaan Perpustakaan Desa Melalui Pojok Baca untuk Meningkatkan Literasi Siswa Sekolah Dasar Desa Jetis Kecamatan Besuki Kabupaten Situbondo - Hikmatul Hasanah; Muhammad Aminuddin; Aulia Maulidatul Faizah; Nala Munirotus Syli; Siti Mufidatul Hasanah; Nurma Dianan Veronika; Dwi Farah Zainabila; Dimas Cucu Mujadid; M. Fikrih Arifin; Dina Salsabila; Fardanila Utari; Sonia Ali; Zonariyah Nadzwa; Naura Ula Salsabila (ADM : Jurnal Abdi Dosen dan Mahasiswa, 2025)
Empowering village libraries through reading corners is a crucial strategy to support increased literacy among the community, particularly among elementary school students living in rural areas. Based on initial observations conducted in Jetis Village, Besuki District, Situbondo Regency, it was found that the low reading interest among elementary school students was caused by limited reading facilities and a lack of available reading materials. The suboptimal utilization of the existing library space in the village exacerbated this condition. Pengabdi took the initiative to establish a reading corner as part of an effort to enhance the village library. This activity was carried out through the PAR (Participatory Action Research) method involving lecturers, students, teachers, the village government, and the community. The reading corner not only aims to increase access to reading materials but also creates a comfortable, interesting, and conducive learning atmosphere. The results of this activity showed that the presence of a reading corner can increase student visits to the library and gradually encourage reading interest. This program successfully built a strong foundation for the development of village libraries as centers for community learning activities. Going forward, this next program will require cross-stakeholder collaboration to ensure collection maintenance, improve the quality of reading materials, and actively involve the community in promoting a reading culture. Therefore, the reading corner is an effective solution for improving literacy among elementary school students in Jetis Village.